A Novel PRKAR1A Mutation in Korean Carney Complex Family - Rhee, S. Y.; Kwon, H. S.; Lee, J. H.; Woo, J.-T.; Kim, M. K.; Lim, Y. J.; Rhee, B. A.; Koh, S. H.; Lee, S.; Lee, M.-H.; Kim, D. Y.; Chon, S.; Oh, S.; Kim, S. W.; Kim, J.-W.; Kim, Y. S.; Choi, Y. K. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Carney complex (CNC) is an autosomal dominant hereditary or sporadic multiple neoplastic syndrome that shows variable clinical symptoms. Generally, CNC appears as skin pigmentation, cardiac or cutaneous myxomas, and multiple endocrine tumours. We performed an extensive evaluation of 9 individuals within 1 family in whom CNC was suspected. Among them, 5 had CNC with various clinical manifestations. We also performed mutational analysis of suspected genes in these patients. Although all patients were members of the same family, variable CNC-related manifestations were observed in each patient. An analysis showed a novel deletion mutation (c.537delA) in exon 6 of the PRKAR1A gene in the patients. Based on our results, the patients were determined to have CNC type I. This is the first such mutational report in Korea.
Keywords: cyclic-AMP-dependent protein kinase RIalpha subunit; myxoma; thyroid neoplasm